1977
DOI: 10.1128/iai.16.2.550-556.1977
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the lipopolysaccharide of Neisseria gonorrhoeae

Abstract: Analysis of glycose and fatty acid content of lipopolysaccharide extracted from 38 strains of Neisseria gonorrhoeae indicated that glycoses common to colonial types 1 to 5 were glucose, mannose, and galactose. N-acetylneuraminic acid, 2keto-3-deoxyoctulosonic acid (KDO), glucosamine, and galactosamine were also invariably present. Virulent colonial types 1 and 2 contained no rhamnose, in contrast to avirulent types 3 to 5 and several strains ofthe nonpathogenic species N. sicca and N. lactamica. Fucose, charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Mo-xted to, grame drzakowski et al found numerous bactericidal ted to, gram-fractions from chromatographically fractionated ainca previous granule contents and went on to more comien amous pletely describe a fraction (valley AB from a cient amounts Sephadex G-100 column) that contained a po-T isedkibitegd tent bactericidal cationic protein with an appar-P5 M) present ent molecular weight of approximately 36,500 (6, ion by CCP of 7) Gram-negative bacteria, possessing lipopolyhio cOPacofi sacchande with the Ra chemotype, appeared to cherechla osli have similar sensitivities to Modrzakowski's valthereas loss of ley AB protein and Weiss's B/PI. The gonococci ilrty in gono-used in this report apparently have the Ra chemcurs only after d decrease in otype lipopolysaccharide (12,24) and appear to (iv) The bac-react to partially purified B/PI protein with the ted by heating same sensitivity as Ra mutants of E. coli (mangonococcicidal uscript in preparation). -0.179 (0.05) 0.580 (0.02) a At 0 min, the spectrophotometer was zeroed at 550 nm to the PBS control containing gonococci and was used as the blank for the other assays.…”
Section: Resultsmentioning
confidence: 77%
“…Mo-xted to, grame drzakowski et al found numerous bactericidal ted to, gram-fractions from chromatographically fractionated ainca previous granule contents and went on to more comien amous pletely describe a fraction (valley AB from a cient amounts Sephadex G-100 column) that contained a po-T isedkibitegd tent bactericidal cationic protein with an appar-P5 M) present ent molecular weight of approximately 36,500 (6, ion by CCP of 7) Gram-negative bacteria, possessing lipopolyhio cOPacofi sacchande with the Ra chemotype, appeared to cherechla osli have similar sensitivities to Modrzakowski's valthereas loss of ley AB protein and Weiss's B/PI. The gonococci ilrty in gono-used in this report apparently have the Ra chemcurs only after d decrease in otype lipopolysaccharide (12,24) and appear to (iv) The bac-react to partially purified B/PI protein with the ted by heating same sensitivity as Ra mutants of E. coli (mangonococcicidal uscript in preparation). -0.179 (0.05) 0.580 (0.02) a At 0 min, the spectrophotometer was zeroed at 550 nm to the PBS control containing gonococci and was used as the blank for the other assays.…”
Section: Resultsmentioning
confidence: 77%
“…It has been shown that T1 variants may contain S type lipopolysaccharide (21), in addition to R type lipopolysaccharide (22,28), the only type found in T4 variants. Furthermore, T1 variants have a larger amount of acidic glycoses, N-acetylneuraminic acid and 2-ketodeoxyoctulosonic acid than T4 variants (30).…”
Section: Resultsmentioning
confidence: 95%
“…minal tetrasaccharide (lacto-N-neotetraose, LNnT) of paragloboside (nLc4Cer), a glycosphingolipid precursor ofthe major human blood group antigens (10), and terminates in the disaccharide N-acetyllactosamine (LacNAc) . Although complete chemical structures have not been reported for the oligosaccharides of any gonococcal LOS, several laboratories have reported that the LOS of various strains were composed ofdifferent ratios ofthe same monosaccharides (Gal, Glc, G1cNAc, Hep, dOclA) as meningococcal LOSS (11)(12)(13)(14)(15)(16) .…”
mentioning
confidence: 99%